PENILAIAN KERENTANAN FISIK, SOSIAL DAN EKONOMI DUSUN-DUSUN DI SEKITAR KALI PUTIH TERHADAP BANJIR LAHAR GUNUNGAPI MERAPI - , PANJI NUR RAHMAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vulnerability assessment is one step in disaster mitigation . Vulnerability assessment serves to identify the ability of communities to cope with disasters . Vulnerability assessment is done in terms of physical , social and economic . The purpose of this study was to assess the physical and socio- economic vulnerability in the study area . Furthermore, the vulnerability variables are processed to determine total vulnerability. Vulnerability assessment is done with the âdusunâ as the unit of analysis . There are 68 dusun are the unit of analysis in this study . Dusun were selected based on the location of the entry into KRB I and KRB II around Kali Putih river . The method of analysis is use a Spatial Multi- Criteria Evaluation Method ( SMCE ) . Physical vulnerability in the study area is dominated by a village with a high degree of vulnerability . For socio-economic vulnerability , the dusun in the area most of the research has a low vulnerability. Determination of total vulnerability classes conducted by three scenarios , namely physical vulnerability scenarios with a higher weight than the socio-economic vulnerability